Problematik Pengaturan Frasa Gangguan Lainnya Sebagai Syarat Pelaksanaan Pemilu Lanjutan Dan Pemilu Susulan (Studi Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum) - Muhammad Erfa Redhani; Retno Widiastuti; Aprillia Wahyuningsih (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
The criteria for postponing general elections in Indonesia currently do not have legal certainty, this is because there are still multiple interpretations of the phrase "other interference" in Article 431 and Article 432 of Law Number 7 of 2017 concerning General Elections (Law No. 7 of 2017). The phrase "other interference" in the context of further elections and subsequent elections raises the potential for elections "to be postponed" not in accordance with the mandate of Article 22E paragraph (1) of the 1945 NRI Constitution which regulates elections to be held every five years. This research was raised to be discussed in a limited manner based on 2 (two) problem formulations, namely, 1) how problematic is the regulation of other nuisance phrases as a condition for the implementation of further elections and subsequent elections in Law No. 7 of 2017?; and 2) how is the idea of improving the regulation of other nuisance phrases as a condition for the implementation of further elections and subsequent elections in Law No. 7 of 2017? This research is a normative juridical research with a statutory approach (statute approach), conceptual approach (conceptual approach) and case approach (case approach). The results showed, first, the phrase "other disorders" contained in Law No. 7 of 2017 is an ambiguous or multiinterpretive sentence can lead to abuse of power to postpone elections. Second, it is necessary to limit the regulation of other nuisance phrases as a condition for the implementation of further elections and subsequent elections in Law No. 7 of 2017.